On the stability and null-controllability of an infinite system of linear differential equations - Azamov, Abdulla; Ibragimov, Gafurjan; Mamayusupov, Khudoyor; Ruziboev, Marks (Springer, 2021)
In this work, the null controllability problem for a linear system in ℓ2 is considered, where the matrix of a linear operator describing the system is an infinite matrix with λ∈R on the main diagonal and 1s above it. We show that the system is asymptotically stable if and only if λ ≤− 1, which shows the fine difference between the finite and the infinite-dimensional systems. When λ ≤− 1 we also show that the system is null controllable in large. Further we show a dependence of the stability on the norm, i.e. the same system considered ℓ∞ is not asymptotically stable if λ = − 1.